2011
DOI: 10.1111/j.1468-1293.2011.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

First trimester maternal uterine artery Doppler examination in HIV-positive women

Abstract: The aim of the current study was to assess the effect of maternal HIV infection, treated or untreated, on the degree of placental invasion, as assessed by the pulsatility index of the uterine arteries during a Doppler examination at 11 1 0 -13 1 6 weeks' gestation. MethodsThis was a nested case-control study in which a uterine artery Doppler examination was performed in the first trimester in 76 HIV-positive women. Each woman was matched with 30 HIV-negative women. As the pulsatility index of the uterine arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, regarding HIV-infected patients, some ART has been associated with endothelial dysfunction and CVD 44 . Nevertheless, Torriani et al (2008) 45 , comparing three different randomized ARV regimens among HIV-infected naïve individuals, in order to evaluate the effect of these ARV on endothelial function, noticed rapid improvement of endothelial function after ARV administration. Savvidou et al (2011) evaluated the uteroplacental circulation by Doppler ultrasound of HIV-infected and non-infected pregnant women in the first trimester of gestation – a probable early biomarker to predict PE –, with the aim to assess the degree of placental invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regarding HIV-infected patients, some ART has been associated with endothelial dysfunction and CVD 44 . Nevertheless, Torriani et al (2008) 45 , comparing three different randomized ARV regimens among HIV-infected naïve individuals, in order to evaluate the effect of these ARV on endothelial function, noticed rapid improvement of endothelial function after ARV administration. Savvidou et al (2011) evaluated the uteroplacental circulation by Doppler ultrasound of HIV-infected and non-infected pregnant women in the first trimester of gestation – a probable early biomarker to predict PE –, with the aim to assess the degree of placental invasion.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Torriani et al (2008) showed improved endothelial function after ARV administration [97]. Additionally, Savvidou et al (2011) found normal placental perfusion among HIV-infected women, with uncomplicated pregnancies, receiving and not receiving HAART [98]. In contrast, a study done by Sebitloane et al (2017) evaluating the effect of HAART on HDP showed that, among all women with HIV, a greater risk of mortality due to HDP was reported among those who received HAART compared with those who did not [99].…”
Section: Highly Active Anti-retroviral Therapymentioning
confidence: 99%